Risk Factors for Thyroid Dysfunction in Patients with Advanced Non-Small-Cell Lung Cancer Treated with PD-1 Antibody. (12th August 2022) - Zhang, Junjun; Lou, Jing
Abstract : Objective . To analyze the health status of thyroid function in patients with advanced non-small-cell lung cancer cured with PD-1 antibody and to explore the risk factors of thyroid dysfunction. Methods . 100 patients from Hunan Provincial People's Hospital with advanced non-small-cell lung cancer hospitalized from January 2021 to March 2022 were selected. All patients were treated with a PD-1 antibody. The differences in sex, age, operation history, chemotherapy history, radiotherapy history, and thyroid nodules between patients with abnormal thyroid function and normal thyroid function after treatment were compared. Moreover, the risk factors of thyroid dysfunction were analyzed. Results . The proportion of women in the normal thyroid function group was lower compared to the abnormal thyroid function group. And the proportion of patients with the course of the disease within 1 year in the normal thyroid function group was higher compared to the abnormal thyroid function group. The incidence of thyroid color ultrasound nodules in the normal thyroid function group was remarkably higher compared to the abnormal thyroid function group (P < 0.05 ). The proportion of patients with nodules in the abnormal thyroid function group was remarkably higher compared to the normal thyroid function group. Among the 36 patients who developed abnormal thyroid function, the incidence of hyperthyroidism (hyperthyroidism) and subclinical hyperthyroidism (subclinical hyperthyroidism) was 33.33%. The incidence of hypothyroidism (hypothyroidism) and hypothyroidism (subclinical hypothyroidism) was 66.66%. The cumulative incidence rates after 3 cycles, 6 cycles, and 12 cycles were 63.88%, 83.33%, and 94.44%, respectively. T4 and FT3 levels decreased more than the normal group following therapy. The results showed that females, course of disease more than one year, and thyroid nodule were independent risk factors of thyroid dysfunction. Conclusion . Female gender, disease duration of more than 1 year, and thyroid nodules were independent risk factors for thyroid dysfunction after PD-1 antibody therapy. Therefore, clinical treatment should focus on patients with the above factors, and early intervention should be implemented to avoid the occurrence of thyroid dysfunction after PD-1 antibody treatment.